PERCEPTION OF FAMILY AS CAREGIVER ABOUT THE IMPLEMENTATION OF ORAL CARE IN CARING FOR STROKE PATIENTS IN MEDAN CITY: A PRELIMINARY ACTION RESEARCH - Bitcar Dalimunthe; Setiawan Setiawan; Cholina Trisa Siregar; Dudut Tanjung; Ikhsanuddin Ahmad Harahap (Alta Dharma Publisher, 2019)
Stroke sufferers continue to increase every year and become polemic in various countries. Stroke is the second most common cause of death after heart disease. Stroke sufferers cause disruption of physical mobility, so they need help to carry out daily activities, one of which is the implementation of oral care, which is still minimal. The study aimed to describe the perception of family caregivers in implementing oral care among stroke patients in Medan city areas. A qualitative with phenomenology approach was applied in this study. The study was conducted in the Health Centre of Medan Deli, in April-August 2018. Twelve participants were recruited using purposive sampling. Data collection used focus group discussion (FGD). We analyzed the data by using the thematic analysis. The results of the study found that four themes, namely: 1) Caregiver knowledge in the implementation of oral care for stroke patients at home is not good, 2) The process of implementing oral care by caregiver for stroke patients at home is less optimal, 3) Family obstacles in carrying out oral care for stroke patients at home, 4) Expectations and suggestions in the implementation of oral care for stroke patients at home. Expected of research to developing or making a guide to the implementation of oral care as health education for families as caregivers in treating stroke patients at home, so that problems of oral care for stroke patients can be minimized. Keywords: oral care, families caregivers, and stroke patients.